The potential of green technology application in the outdoor built environment - Izumi, Mohamad Azim; Abdul Razak, Nazrul Nizam; Abu Bakar, Aniza (2015)
Green Technology (GT) appears due to the occurrence of various environmental issues caused by the negative impacts of human involvement. Global warming, climate change, and resource depletion are the most prominent issues which relates to the built environment. In Malaysia, the green approach to mitigate these issues however, does not truly focused on the outdoor built environment. This paper is focusing on finding the potential of GT application in the outdoor built environment. The study is important in identifying what types of GT is applicable to outdoor environment based on their criteria. To achieve the aim of the study, the fieldwork was conducted around academic building area of International Islamic University Malaysia (IIUM). Observation was chosen as the method of study. The type of GT for the outdoor environment were identified based on the literature review, continued by identifying the types of GT to be applied on site, based on its function and design criteria. Then, potential sites were identified for the GT to be applied. Those characteristic identified before were confirmed on-site, in order to identify the potentiality of the site on applying GT. There are aspects and variable that were considered in this research which are; surface temperature, building orientation, rainfall quantity & timing, space function, physical characteristic of the location and site topography. The research proved that the site is very potential for the GT to be applied.